Avaliação da qualidade da água do reservatório de Sobradinho através da análise de componentes principais - Soares, Cleide Cruz (2022)
Among the various forms of water use, there is the building of dams which, in addition to aiming at social well-being, sometimes it generates hydroelectric power, and can also produce negative effects. In this sense, it is extremely important to monitor the quality of water properly and periodically in these regions. This study aims at applying multivariate analysis to extract information from a set of water quality data collected from the Sobradinho dam, to assess potential factors that alter water quality, considering a historical series. The methodology consisted of applying the multivariate statistical analysis at one of the collection points of the 1st São Francisco River Monitoring Program, under reduced flow, between the years 2016 and 2021, considering physicochemical and phytoplankton variables in addition to data from precipitation and flow. The influence of drastic precipitation changes and the water reservoir flow control is made especially salient through Pearson’s correlation matrix. Considering the physical-chemical parameters, there were outstanding variations in electrical conductivity, which did not follow seasonal trends; in alkalinity, which has increased over the years, probably due to the decomposition of organic matter, especially in periods with low water exchange; in the trend of occurrence of the nitrification process, between 2016 and 2018, and the occurrence of the ammonification process, between 2019 and 2021, the latter with reduced availability of oxygen in the water. In this way, it was possible to conclude that there were no seasonal differences regarding the evaluation of the parameters studied, however, over the years, it is clear that the quality of the water has undergone negative changes that can make unfeasible its use for noble purposes. Therefore, it is extremely important that, in addition to monitoring, preventive measures must be taken to recover the waters of the São Francisco River basin, especially the waters that make up the Sobradinho dam.